2022
DOI: 10.3390/brainsci12101299
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Bilateral Eye Movements on Memory Retrieval in Ageing and Dementia

Abstract: It has been reported that performing bilateral eye movements for a short period can lead to an enhancement of memory retrieval and recall (termed the “saccade induced retrieval effect (SIRE)”). The source of this effect has been debated within the literature and the phenomenon has come under scrutiny as the robustness of the effect has recently been questioned. To date investigations of SIRE have largely been restricted to younger adult populations. Here, across two experiments, we assess the robustness and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…While some studies have failed to replicate a memory improving effect of eye movements (e.g., Polden & Crawford, 2022), the metanalyses conducted by Qin et al (2021) found moderate effect sizes across published studies (Cohen's d = .45). There are several important things to note about these findings.…”
Section: Recent Findings Related To Handedness and Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have failed to replicate a memory improving effect of eye movements (e.g., Polden & Crawford, 2022), the metanalyses conducted by Qin et al (2021) found moderate effect sizes across published studies (Cohen's d = .45). There are several important things to note about these findings.…”
Section: Recent Findings Related To Handedness and Memorymentioning
confidence: 99%
“…For example. Polden and Crawford (2022) used an estimated effect size of .495 (already larger than Qui et al’s metaanalysis effect size of .45) to determine a sample size of sufficient statistical power. However, sufficient power has frequently been assumed to be .80, meaning that researchers were willing to accept up to a 20% chance that a real effect would not be detected.…”
Section: Recent Findings Related To Handedness and Memorymentioning
confidence: 99%
“…One group of studies investigated the possible contributions of specific stimuli, training protocols, and recognized effects to the enhancement of memory retrieval and/or recall. In particular, across two experiments, Polden and Crawford [ 4 ] reported no memory retrieval enhancement effects for the “saccade-induced retrieval effect” (SIRE) in both normal and pathological aging, highlighting the SIRE effect’s apparent lack of strength. On the contrary, both curiosity [ 5 ] and affective information [ 6 ] may affect information processing by improving memory for trivia answers and incidental memory for unrelated faces, simplifying information processing by both prioritizing positive information and de-prioritizing negative information, respectively.…”
mentioning
confidence: 99%